2007
DOI: 10.1197/j.aem.2007.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Communicating in the “Gray Zone”: Perceptions about Emergency Physician–hospitalist Handoffs and Patient Safety

Abstract: Objectives: To identify the perceptions of emergency physicians (EPs) and hospitalists regarding interservice handoff communication as patients are transferred from the emergency department to the inpatient setting.Methods: Investigators conducted individual interviews with 12 physicians (six EPs and six hospitalists). Data evaluation consisted of using the steps of constant comparative, thematic analysis.Results: Physicians perceived handoff communication as a gray zone characterized by ambiguity about patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 26 publications
1
70
0
Order By: Relevance
“…Handoffs between physicians-in-training (3)(4)(5)(6), between nurses (7)(8)(9), and between ancillary staff such as respiratory therapists (7) are well-described in the literature. In contrast, transitions of care at the attending physician level have been less well studied (10)(11)(12)(13). With the exception of one single-center study (14), the handoff practices of intensivists have not been reported, and we know of no descriptions of how attending handoffs ought to be conducted.…”
mentioning
confidence: 98%
“…Handoffs between physicians-in-training (3)(4)(5)(6), between nurses (7)(8)(9), and between ancillary staff such as respiratory therapists (7) are well-described in the literature. In contrast, transitions of care at the attending physician level have been less well studied (10)(11)(12)(13). With the exception of one single-center study (14), the handoff practices of intensivists have not been reported, and we know of no descriptions of how attending handoffs ought to be conducted.…”
mentioning
confidence: 98%
“…20,57 The IoM report states that ineffective handover has been identified as one of the leading causes of medical error in the ED. 1 Problems with shift handover in the emergency department Several studies have investigated shift handover in the ED.…”
Section: Handover and Communication In Emergency Carementioning
confidence: 99%
“…[20][21][22][23][24] This includes not only the 'telling of the story' by the person giving the handover, but also interpretation and confirmation of the story, and the development of a mental model by the recipient of the handover, which allows seamless transition of care. 22 In addition, handover can serve further functions other than simple information transfer.…”
Section: Handover As a Risk To Patient Safetymentioning
confidence: 99%
“…and recorded the responses, including (1) a brief description of the event, (2) factors the resident believed may have caused or contributed to the event, (3) whether the patient was passed off as already having a disposition and requiring no expected action on the part of the new physician or a patient requiring some follow-up action, and (4) if they believe there was any harm to the patient as a result of the error.…”
Section: Methodsmentioning
confidence: 99%
“…1 The transition of patient care, or ''hand off,'' between 2 physicians is an area of the medical system known to have risk for error. 2 It has not yet been definitively determined what educational steps are necessary for residents to become competent at minimizing errors during transitions of care. One necessary step of resident education is for the resident to first perceive and label when an error occurs.…”
Section: Introductionmentioning
confidence: 99%